DIVERSIFIKASI SUMBER HIJAUAN PAKAN UNTUK MENINGKATKAN KETERSEDIAAN DAN KUALITAS PAKAN SAPI BALI - Trisnadewi, A.A.A.S.; Suarna, I.W.; Cakra, I.G.L.O.; Budiasa, I.K.M.; Wirawan, I.W.; Sugiantini, N.L.M. (Buletin Udayana Mengabdi; Vol 23 No 5 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i05.p01, 2023)
Pengotan Village is geographically located at an altitude of 800 – 1100 m with an average temperature of 28°C . Problems faced in the provision of forage feed is the fluctuating forage production during the rainy and dry seasons, so the quatity and quality of forage that offering is hard to fulfill to ruminant especially bali cattle. Diversification of forage for ruminants is needed to: 1) overcoming the obstacle of forage availability due to limited land for cultivation of forage feed, 2) improve the forage quality through combination of grass and legumes as a source of forage, so that the nutritional needs of ruminants can be met, and 3) reduce the influence of antinutritional on certain forages through diversification of forage because it could be the limiting factor if given in excessive amount to ruminant especially bali cattle. Methods of activities carried out through counseling and discussion, making demoplot forage and seed deployment especially introduce grass and legum to be developed in Pengotan Village. The service was attended by 18 participants and attended by representatives from the village office, socialization and counseling were carried out on the diversification of forage sources to increase the availability and quality of forage feed. In the service activity, demonstration plots for planting forage and dissemination of forage such as dwarf elephant grass (Pennisetum purpureum cv. Mott), Clitoria ternatea and Centrosema pubescens which were carried out together with farmers. Keywords: forage diversification, grass, leguminose, bali cattle